Therapeutic Approaches to Alzheimer’s Type of Dementia: A Focus on FGF21 Mediated Neuroprotection - Taliyan, Rajeev; Chandran, Sarathlal K.; Kakoty, Violina (Current Pharmaceutical Design, 2019)
Neurodegenerative disorders are the most devastating disorder of the nervous system. The pathological basis of neurodegeneration is linked with dysfunctional protein trafficking, mitochondrial stress, environmental factors and aging. With the identification of insulin and insulin receptors in some parts of the brain, it has become evident that certain metabolic conditions associated with insulin dysfunction like Type 2 diabetes mellitus (T2DM), dyslipidemia, obesity etc., are also known to contribute to neurodegeneration mainly Alzheimer’s Disease (AD). Recently, a member of the fibroblast growth factor (FGF) superfamily, FGF21 has proved tremendous efficacy in diseases like diabetes mellitus, obesity and insulin resistance (IR). Increased levels of FGF21 have been reported to exert multiple beneficial effects in metabolic syndrome. FGF21 receptors are present in certain areas of the brain involved in learning and memory. However, despite extensive research, its function as a neuroprotectant in AD remains elusive. FGF21 is a circulating endocrine hormone which is mainly secreted by the liver primarily in fasting conditions. FGF21 exerts its effects after binding to FGFR1 and co-receptor, β-klotho (KLB). It is involved in regulating energy via glucose and lipid metabolism. It is believed that aberrant FGF21 signalling might account for various anomalies like neurodegeneration, cancer, metabolic dysfunction etc. Hence, this review will majorly focus on FGF21 role as a neuroprotectant and potential metabolic regulator. Moreover, we will also review its potential as an emerging candidate for combating metabolic stress induced neurodegenerative abnormalities.
Keywords: diabetes mellitus